A randomised Phase II trial of carboplatin and gemcitabine ± vandetanib in first‐line treatment of patients with advanced urothelial cell cancer not suitable to receive cisplatin. (19th May 2020) - Jones, Robert; Crabb, Simon; Chester, John; Elliott, Tony; Huddart, Robert; Birtle, Alison; Evans, Linda; Lester, Jason; Jagdev, Satinder; Casbard, Angela; Huang, Chao; Madden, Tracie‐Ann; et al.
Abstract : Objectives: To assess the efficacy and tolerability of the dual epidermal growth factor receptor/vascular endothelial growth factor receptor inhibitor, vandetanib, in combination with carboplatin and gemcitabine in the first‐line treatment of patients with advanced transitional cell carcinoma urothelial cancer (UC) who were unsuitable for cisplatin. Patients and methods: From 2011 to 2014, 82 patients were randomised from 16 hospitals across the UK into the TOUCAN double‐blind, placebo‐controlled randomised Phase II trial, receiving six 21‐day cycles of intravenous carboplatin (target area under the concentration versus time curve 4.5, day 1) and gemcitabine (1000 mg/m 2 days 1 and 8) combined with either oral vandetanib 100 mg or placebo (once daily). Progression‐free survival (PFS; primary endpoint), adverse events, tolerability and feasibility of use, objective response rate and overall survival (OS) were evaluated. Intention‐to‐treat and per‐protocol analyses were used to analyse the primary endpoint. Results: The 82 patients were randomised 1:1 to vandetanib ( n = 40) or placebo ( n = 42), and 25 patients (30%) completed six cycles of all allocated treatment. Toxicity Grade ≥3 was experienced in 80% ( n = 32) and 76% ( n = 32) of patients in the vandetanib and placebo arms, respectively. The median PFS was 6.8 and 8.8 months for the vandetanib and placebo arms, respectively (hazard ratio [HR] 1.07, 95% confidence interval [CI] 0.65–1.76; P  = 0.71); the median OS was 10.8 vs 13.8 months (HR 1.41, 95% CI 0.79–2.52; P  = 0.88); and radiological response rates were 50% and 55%. Conclusion: There is no evidence that vandetanib improves clinical outcome in this setting. Our present data do not support its adoption as the regimen of choice for first‐line treatment in patients with UC who were unfit for cisplatin.